Playing with lives under the guise of fair play: the safe country of origin policy in the EU and Canada. (2018) - Zyfi, Jona; Atak, Idil
The safe country of origin (SCO) policy has been implemented by the European Union (EU) and Canada as a way to deal with a backlog of asylum applications, increase efficiency, reduce administrative costs and exclude fraudulent refugee claims. The concept is founded on the assumption that a democratic country with an adequate human rights record is safe for individuals because there is generally no risk of persecution. While this attempt at creating more efficient asylum procedures may seem sensible in theory, an in-depth analysis will reveal that the practice is a prejudicial, exclusionary, and dangerous development that could potentially deny asylum to those who are in genuine need of international protection. Contributing to the existing body of literature, our paper provides a comparative analysis of how SCO is rationalised in Canada and the EU. We argue that the policy is a political response to unwanted migration and a migration management tool used to deter and limit asylum applications from what States deem as 'bogus' refugees, while facilitating the removal of these individuals. Whether these goals have been attained remains debatable. However, as currently applied, the SCO policy is detrimental to the human rights of asylum seekers.